Laser‐Induced Graphene Superhydrophobic Surface Transition from Pinning to Rolling for Multiple Applications. Issue 4 (24th February 2022) - Han, Yingkuan; Han, Yunrui; Huang, Yuzhen; Wang, Chao; Liu, Hong; Han, Lin; Zhang, Yu
Abstract: The fabrication and applications of superhydrophobic surfaces (contact angle >150°,  sliding angle <10°) have attracted worldwide interest with respect to materials and devices. In this work, the laser‐induced graphene (LIG) superhydrophobic surface transition from pinning to rolling via an extremely simple solvent treatment of LIG in air is reported. By adding a certain solvent (e.g., ethanol) to the surface, the LIG superhydrophobic surface changes from pinning (sliding angle = 180°) to rolling (sliding angle <6°), which is attributed to the chemically changed surface properties and surface morphology of LIG. Three applications are demonstrated with the developed superhydrophobic LIG, including surface‐enhanced Raman spectroscopy, water–oil separation, and anti‐icing. Abstract : The superhydrophobic laser‐induced graphene surface changes from pinning to rolling with ethanol treatment, which contributes to the surface chemical composition and surface morphology change. Applications including surface‐enhanced Raman scattering analysis, water–oil separation, and anti‐icing are demonstrated using the developed superhydrophobic laser‐induced graphene surface.